2018
DOI: 10.1111/1365-2745.12958
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits and environmental characteristics drive the degree of competitive intransitivity in European saltmarsh plant communities

Abstract: Competitive intransitivity, the existence of loops in competitive hierarchies, is one mechanism that can promote the local coexistence of competitors and maintain high local species diversity, although its prevalence and importance remain largely unknown. A full understanding of local community assembly needs knowledge of how transitive and intransitive competitive interactions are linked to species functional traits and the strength of biotic and abiotic filters. We apply a recently developed statistical tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 65 publications
6
39
0
Order By: Relevance
“…() suggest strong links between intransitive competition and the evolution of greater functional trait divergences in a given clade, which is supported by the empirical, bivariate relationships found by Ulrich et al. () in saltmarsh plant communities. Soliveres et al.…”
Section: Beyond Species Coexistence: What Are the Consequences Of Intsupporting
confidence: 54%
See 1 more Smart Citation
“…() suggest strong links between intransitive competition and the evolution of greater functional trait divergences in a given clade, which is supported by the empirical, bivariate relationships found by Ulrich et al. () in saltmarsh plant communities. Soliveres et al.…”
Section: Beyond Species Coexistence: What Are the Consequences Of Intsupporting
confidence: 54%
“…Most metrics of intransitivity consider competitive exclusion as a binary process: a species either wins or loses in competition. However, two of the studies in this special feature (Gallien, Landi, Hui, & Richardson, ; Ulrich, Kubota, Piernik, & Gotelli, ) show the need to consider more continuous measurements of competition (see also Gallien, Zimmermann, Levine, & Adler, ). If we take a more continuous view, there are almost endless possibilities for how a simple three‐species (A, B, C) competition network can organize, ranging from pure (or “strong”) hierarchy (A ≫ B ≫ C, A ≫ C) to strong intransitivity (A ≫ B ≫ C ≫ A) and everything in between (e.g.…”
Section: A Short Story Of a Difficult Task: How Can We Measure Intranmentioning
confidence: 99%
“…If functional traits of species do affect their likelihood of engaging in intransitive competition then we might expect changes in intransitivity to also feed‐back to affect trait distributions. Previous studies have shown an increase in functional trait diversity under intransitive competition (Maynard, Bradford, et al., ; Ulrich et al., ), but these changes are not always expected (Gallien, ). Our results suggest that, if intransitive competition is driven by reciprocal competitive advantages (as seems to be the cases for fungi, mosses and bacteria), then it should strongly relate to functionally diverse communities.…”
Section: Discussionmentioning
confidence: 95%
“…C uptake vs. aggressiveness; see also Maynard, Crowther, et al., ). Assuming that functional traits were not only related only to competitive ranks, but also to the different ways by which different species compete for resources (Kraft et al., ; Kunstler et al., ; see also Ulrich et al., , Supplementary Material ), this could explain the positive effects of trait variation in the intransitivity level of triplets of fungi, mosses or bacteria (Figure ) even when the variance in competitive ranks had a negative effect. However, when competing species are too different in their ranks (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation